Two new species of Paravelia Breddin, 1898 and distributional notes concerning the Veliidae from Minas Gerais State, Brazil (Insecta: Hemiptera: Heteroptera: Gerromorpha) - Moreira, Felipe Ferraz Figueiredo; Barbosa, Julianna Freires (Zootaxa, 2012)
Paravelia lanemeloi sp. nov. and P. nieseri sp. nov. are described. Microvelia inannana, Oiovelia brasiliensis, Rhagoveliamodesta, R. novana, R. sooretama, R. teresa, R. vaniniae, and R. zela are recorded for the first time from Minas GeraisState. Additional records are presented for M. longipes, M. pulchella, R. aiuruoca, R. hambletoni, R. macta, R. robusta, R. sabrina, R. triangula, R. trianguloides, and R. turmalis.